2018
DOI: 10.1093/inthealth/ihy092
|View full text |Cite
|
Sign up to set email alerts
|

Addition of mHealth (mobile health) for family planning support in Kenya: disparities in access to mobile phones and associations with contraceptive knowledge and use

Abstract: Background Recently mobile health (mHealth) has been implemented in Kenya to support family planning. Our objectives were to investigate disparities in mobile phone ownership and to examine the associations between exposure to family planning messages through mHealth (stand-alone or combined with other channels such as public forums, informational materials, health workers, social media and political/religious/community leaders’ advocacy) and contraceptive knowledge and use. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 21 publications
4
30
0
Order By: Relevance
“…However, the type of mobile phone that the patients own may not be smartphones to support an upload of needed software. Such challenges were also reported elsewhere in Kenya 108 110 and Tanzania 111 where there exist similar socioeconomic disparities in mobile phone ownership in support of the implementation of mHealth.…”
Section: Discussionsupporting
confidence: 66%
“…However, the type of mobile phone that the patients own may not be smartphones to support an upload of needed software. Such challenges were also reported elsewhere in Kenya 108 110 and Tanzania 111 where there exist similar socioeconomic disparities in mobile phone ownership in support of the implementation of mHealth.…”
Section: Discussionsupporting
confidence: 66%
“…The design may also consider incorporation of motivational messaging and allow for interactive communication ( 59 ). Ownership of mobile phones is increasing, at a prevalence of 71% in Uganda ( 60 – 62 ). The adoption of mhealth strategies for FP, however, raises some ethical concerns, such as confidentiality or data security.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that, although there is increasing evidence that mobile phones have the potential to improve family planning literacy through family planning text messages (43,44), a greater proportion of this study's participants reported not being aware of such an opportunity. The ndings demonstrate further that the few women who were aware of the opportunity and have subscribed to family planning text message services tend to ignore the messages sent to them through their mobile phones.…”
Section: Discussionmentioning
confidence: 82%